Treatment of avulsion fracture of posterior cruciate ligament tibial insertion by minimally invasive approach in posterior medial knee - Guo, Huihui; Zhao, Yao; Gao, Liang; Wang, Chen; Shang, Xianbo; Fan, Haitao; Cheng, Wendan; Liu, Chang (Frontiers in Surgery, 2023)
Abstract Objective: To explore the feasibility and clinical effect of Posterior minimally invasive treatment of cruciate ligament tibial avulsion fracture. Methods: Posterior knee minimally invasive approach was used to treat avulsion fracture of PCL tibia in 15 males and 11 females. The length of incision, intraoperative blood loss, operation time, postoperative hospital stay, residual relaxation and fracture healing time were analyzed to evaluate the curative effect, learning curve and advantages of the new technology. Neurovascular complications were recorded. During the postoperative follow-up, the International Knee Joint Documentation Committee (IKDC), Lysholm knee joint score and knee joint range of motion (KROM) were recorded to evaluate the function. Results: All 26 patients were followed up for 18-24 months, with an average of 24.42±5.00 months. The incision length was 3-6cm, with an average of 4.04±0.82cm. The intraoperative blood loss was about 45-60ml, with an average of 48.85±5.88ml. The operation time was 39-64min, with an average of 52.46±7.64 min. The postoperative hospital stay was 2-5 days, with an average of 2.73±0.87 days. All incisions healed grade I without neurovascular injury. All fractures healed well with an average healing time of 9.46±1.33 weeks (range, 8-12 weeks). The Lysholm score of the affected knee was 89-98 (mean, 94.12±2.49) at 12-month follow-up. The IKDC score was 87-95 with an average of 91.85±2.19, and the knee range of motion was 129-148 ° with an average of 137.08±5.59°. The residual relaxation was 1-3mm, with an average of 1.46±0.65mm. Conclusion: This minimally invasive method provides sufficient exposure for internal fixation of PCL tibial avulsion fractures without the surgical complications associated with traditional open surgical methods. The process is safe, less invasive and does not require a long learning curve.